The Chicago manual of style / 15th edition - University of Chicago. Press (Chicago : University of Chicago Press, 2003)
Provides information on manuscript preparation, punctuation, spelling, quotations, captions, tables, abbreviations, references, bibliographies, notes, and indexes, with sections on journals and electronic media
The publishing process -- Books and journals -- Overview -- The parts of a book -- The parts of a journal -- Considerations for web-based publications -- Manuscript preparation, manuscript editing, and proofreading -- Overview and process outline -- Manuscript preparation guidelines for authors -- Manuscript editing -- Proofreading -- Illustrations and tables -- Overview -- Illustrations -- Tables -- Rights, permissions, and copyright administration / by William S. Strong -- Overview -- Copyright law and the licensing of rights -- The publishing agreement -- Subsidiary rights and permissions -- The author's responsibilities -- Style and usage -- Grammar and usage / by Bryan A. Garner -- Grammar -- Word usage -- Punctuation -- Overview -- Punctuation in relation to surrounding text -- Periods -- Commas -- Semicolons -- Colons -- Question marks -- Exclamation points -- Hyphens and dashes -- Parentheses -- Brackets and braces -- Slashes -- Quotation marks -- Apostrophes -- Multiple punctuation marks -- Lists and outline style -- Spelling, distinctive treatment of words, and compounds -- Overview -- Plurals -- Possessives -- Contractions and interjections -- Word division -- A and an, o and oh -- Ligatures -- Italics, capitals, and quotation marks -- Compounds and hyphenation -- Names and terms --
Keywords: Printing -- Style manuals; Authorship -- Handbooks, manuals, etc; Writing; Authorship